Impact of Information Threats on Youth Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the social impact of today's various informational threats and ideological attacks on the moral image of young people. Also, in the era of today's information threats, some unpleasant situations that have a negative impact on the education of young people, which have become a high value for thousands of years, and turn young people away from our traditions, such as kindness, prayer, respect for elders and respect for children, are scientific-theoretical from the point of view of spiritual and moral values.